The side effects of different antiembolic agents on the fracture healing and micro-mechanical behavior of the fractured bone - Tunç, Burcu. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2009., 2009)
Fracture of bone is always expected when the stress exposed to body is enough for initiation and propagation of the crack. Due to social lives, increase of life expectancy, wars and accidents the number of bone fracture has increased. One of the problem during healing of the fractured bone is hematoma formation. In order to eliminate hematoma formation, antiembolic agents injection into the body is generally imperative. In this thesis, we deal with the inorganic portion of the bone, treated with and without antiembolic agents. 16 Wistar-Albino male rats were used for the study. Scanning electron microscopy and X-ray di raction technique were applied in order to reveal the e ect of antiembolic agents on the bone fractured followed by healing. It is observed that antiembolic agents helped healing of the fractured bone without defect and crystalline nature of the inorganic part of bone showed phase transitions.| Keywords: bone, fracture, bone healing, heparin, LMWH, enoxaparin, fondaparinux, crystallinity, SEM, XRD
Keywords: Bones.; Fractures.; Heparin.; Scanning electron microscopy.; X-rays -- Diffraction.